NON-DISCLOSURE AGREEMENT IN THE PROCESS OF PROTECTION OF INTANGIBLE PROPERTY - Widerski, Piotr (Scientific Journal of Bielsko-Biala School of Finance and Law, 2016)
The paper explains a legal concept of a non-disclosure agreement (NDA)/confidential disclosure agreement (CDA) as an effective tool for the trade secret protection. Ensuring the confidentiality of important information of a company is its key operation element. An incompetent protection of a secret may cause significant financial and image losses in every institution. In the paper there was taken an attempt to describe both statutory and contractual legal structures applied in order to secure the company’s trade secret. There were also presented the characteristics of a non-disclosure agreement as an innominate agreements. There was discussed the position of such an agreement in the national and international legal system. The paper specifies essential components of such an agreement that should be applied to secure the interests of the parties. The advantages of applying an NDA as a tool that increases both the protection and possibility of claiming compensation were also specifically described.